HUBUNGAN ANTARA PENYESUIAN DIRI DENGAN STUDENT WELL-BEING PADA SISWA DI SMP X KOTA BEKASI - Caroline Angelica; Yulia Fitriani (CV. ADIBA ASIHA AMIRA, 2025)
This study aims to analyze the relationship between self-adjustment and student well-being at SMP X Bekasi City. Self-adjustment, which includes emotional, intellectual, social, and responsibility maturity, is considered to contribute significantly to student well-being which consists of social, cognitive, emotional, physical, personal, and spiritual aspects. Using a quantitative approach and correlational analysis techniques, this study involved 110 respondents using the Cluster Sampling technique. The results showed a positive and significant relationship between self-adjustment and student well-being, where students who are able to adapt effectively tend to have a higher level of well-being. This finding confirms the importance of the school environment in supporting students' self-adjustment to holistically improve their well-being.